THE EFFECT OF L1 MULTIPLE-CHOICE GLOSSES ON READING COMPREHENSION OF NARRATIVE TEXTS (An Ex-post Facto Study in 9th Grade Students at a Junior High School in Kabupaten Bandung) - Try Ayu Nuralam Setiawan (Journal of English and Education, 2015)
The lack of vocabulary is one of the problems that is mostly encountered by students while reading. L1 MCG is one of the solutions to facilitate students in understanding some vocabulary while reading. The purpose of the research is to find out the use of L1 MCG on reading comprehension and to investigate students’ opinion on L1 MCG in the text. Employing ex-post facto design, this study involved 92 ninth graders in a junior high school at Kabupaten Bandung to accomplish two tests namely grouping test and performance test. A grouping test is to classify students into two groups that are L1 MCG group and no gloss group based on students’ ranking score. A performance test is to emphasize the difference in students’ reading comprehension of L1 MCG group and no gloss group. The questionnaires were distributed to collect students’ opinion in L1 MCG group. The result of the research showed that the scores of L1 MCG group was higher than no gloss group and the students suggested that L1 MCG has facilitated their reading comprehension, has motivated them to read. They agreed with using L1 MCG as media on learning activity. Finally, L1 MCG is suggested to facilitate students in understanding the text while reading.